Balancing hope and disappointment: representation, social wellbeing, and the future of small-scale fisheries in Uruguay. Issue 5 (4th July 2021) - Santos, Paula; Trimble, Micaela; Johnson, Derek
ABSTRACT: Fishers need to feel they are valued partners in fisheries and coastal management. In 2012, the multi-stakeholder participatory action research Group POPA (For Small-Scale Fisheries in Piriápolis) held the First Small-Scale Fisheries Festival in Piriápolis, Uruguay. We investigated the change the Festival produced in the social representation of local fishers and how it relates to fishers' wellbeing aspirations. Negative values in fishers' self-perceptions were found. The positive social change triggered by the Festival tackled mainly fishers' material wellbeing aspirations (boats, fishing gear for better catch and better income). We also discuss how the change proved relevant at different transformative scales.